Language and National Integration: The Case of Malaysia and Uganda Confronting New Realities - El-Nagar, Hassan (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2014)
Language and National Integration: The Case of Malaysia and Uganda Confronting New Realities